"Rapunzel, Rapunzel, Lanza Tu Pelo": Storytelling in a Transcultural, Translanguaging Dialogic Exchange. Issue 4 (28th November 2020) - Flynn, Erin E.
ABSTRACT: In this study, we examined story circles to understand how the small‐group activity supports and shapes the storytelling of young students in multicultural, multilingual preschool classrooms. Through a representative example, we show how language development unfolds in the context of a transcultural and translanguaging dialogic exchange of stories. We describe features of increasing linguistic complexity present in students' storytelling as they established affinity‐affirming connections over ideas, shared ways of languaging, and shared ways of storytelling. By examining changes in one student's storytelling in the context of a mixed‐language story circle group, we offer insights into both language development and features of the language ecology in which such changes are supported.